The impact of forecasting accuracy on managing demand uncertainty - 563150 Awaluddin Mohamed Shaharoun; Mohammed K. Omar; International Conference on Robotics, Vision and Parallel Processing for Industrial Automation (1996 : USM, Perak)
36